2022
DOI: 10.1007/s11252-022-01315-7
|View full text |Cite
|
Sign up to set email alerts
|

Topsoil Carbon Stocks in Urban Greenspaces of The Hague, the Netherlands

Abstract: Urbanization influences soil carbon (C) stocks and flows, which, in turn, affect soil-derived ecosystem services. This paper explores soil C storage in urban greenspaces in the Dutch city of The Hague along a transect from the suburban seaside towards the city centre, reflecting a toposequence from dune to peaty inland soils. C storage and C mineralisation potential were evaluated in relation to soil type and greenspace categories. Several soil-quality characteristics were measured, including dissolved organic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…The included studies examined soil carbon using both direct and indirect approaches. Direct studies explicitly focused on carbon stock analysis in urban green areas [4,17,18,21,25,28,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]. The indirect studies deviated from a specific focus on soil carbon as a central theme.…”
Section: Methodologies Used In the Reviewed Articles On Soil Carbon I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies examined soil carbon using both direct and indirect approaches. Direct studies explicitly focused on carbon stock analysis in urban green areas [4,17,18,21,25,28,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]. The indirect studies deviated from a specific focus on soil carbon as a central theme.…”
Section: Methodologies Used In the Reviewed Articles On Soil Carbon I...mentioning
confidence: 99%
“…As mentioned in the introduction, a predominant focus on soil carbon has been studied in the form of SOC [1,2,4,[16][17][18][19]21,22,[26][27][28][29]43,45,[48][49][50][51][52][54][55][56][57][58][59][60][61][62]65,67,[69][70][71][72]74,76,[80][81][82][83] and in the form of Total Carbon [25,50,51,63,65,66,68,73,75,[77]…”
Section: Methodologies Used In the Reviewed Articles On Soil Carbon I...mentioning
confidence: 99%
“…Finally, prediction uncertainty of most soil properties was also higher in urban areas, which can be attributed to limited soil samples and heavily disturbed soils in urban areas. With increasing population growth in an already densely populated country, this highlights the need to map urban soils (Römkens and Oenema, 2004;Vasenev et al, 2014Vasenev et al, , 2021Kortleve et al, 2023). The PICP90 (Table 7) and the PICP (SI) indicated that prediction uncertainty was estimated relatively accurate using QRF, but small differences were found among the predicted soil properties.…”
Section: Quantitative Accuracy Assessmentmentioning
confidence: 99%
“…Prediction uncertainty in most soil properties was also higher in urban areas, which can be attributed to limited soil samples and heavily disturbed soils in urban areas. With increasing population growth in an already densely populated country, this highlights the need to map urban soils (Römkens and Oenema, 2004;Vasenev et al, 2014Vasenev et al, , 2021Kortleve et al, 2023). The PICP90 (Table 7) and the PICP (the Supplement) indicated that prediction uncertainty was estimated relatively accurately using QRF, but small differences were found among the predicted soil properties.…”
Section: Quantitative Accuracy Assessmentmentioning
confidence: 99%